Contemporary fluid management, humidity, and patent ductus arteriosus management strategy for premature infants among 336 hospitals in Asia - Hsieh, Yao-Chi; Jeng, Mei-Jy; Lin, Ming-Chih; Lin, Yuh-Jyh; Rohsiswatmo, Rinawati; Dewi, Rizalya; Chee, Seok Chiong; Neoh, Siew Hong; Velasco, Belen Amparo E.; Imperial, Ma. Lourdes S.; Nuntnarumit, Pracha; Ngerncham, Sopapan; et al. (Frontiers in Pediatrics, 2024)
Objectives The management of patent ductus arteriosus (PDA) is a critical concern in premature infants, and different hospitals may have varying treatment policies, fluid management strategies, and incubator humidity. The Asian Neonatal Network Collaboration (Asian Neo) collected data on prematurity care details from hospitals across Asian countries. The aim of this study was to provide a survey of the current practices in the management of PDA in premature infants in Asian countries. Methods: Asian Neo performed a cross-sectional international questionnaire survey in 2022 to assess the human and physical resources of hospitals and clinical management of very preterm infants. The survey covered various aspects of hospitals resources and clinical management, and data were collected from 337 hospitals across Asia. The data collected were used to compare hospitals resources and clinical management of preterm infants between areas and economic status. Results: The policy of PDA management for preterm infants varied across Asian countries in AsianNeo. Hospitals in Northeast Asia were more likely to perform PDA ligation (p < 0.001) than hospitals in Southeast Asia. Hospitals in Northeast Asia had stricter fluid restrictions in the first 24 hours after birth for infants born at < 29 weeks gestation (p < 0.001) and on day 14 after birth for infants born at < 29 weeks gestation (p < 0.001) compared to hospitals in Southeast Asia. Hospitals in Northeast Asia also had a more humidified environment for infants born between 24 weeks gestation and 25 weeks gestation in the first 72 hours after birth (p < 0.001). A logistic regression model predicted that hospitals were more likely to perform PDA ligation for PDA when the hospitals had a stricter fluid planning on day 14 after birth (Odds ratio (OR) of 1.70 , p = 0.048), more incubator humidity settings (<80% vs 80-89%, OR of 3.35 , p = 0.012 and <80% vs 90-100%, OR of 5.31, p < 0.001). Conclusions: In advanced economies and Northeast Asia, neonatologists tend to adopt a more conservative approach towards fluid management, maintain higher incubator humidity settings and inclined to perform surgical ligation for PDA.